Kinetic Energy Rate of the Rain Drops Based on the Impact Signal Analysis - Moraes, M. C. da S. (2020)
The erosive potential of precipitation can be evaluated by the kinetic energy transferred to the soil by the impact of the rain drop. A kinetic energy rate of the rain drops was estimated by the disdrometer classifying impact signals. This equation in the form of power presented an adjustment measure between the rain rate and rainfall quantity of 97% and 95% for continental and maritime rains, respectively. The exponent of the power equation, initially, shows no dependence on the type of rainfall. However, the multiplicative factor presented variation, which can be adjusted according to rainfall events. This equation was validated by the coefficient of determination, the average absolute error and the confidence error. The kinetic energy of precipitation, associated to certain types of soil, will allow the determination of the potential of the erosion caused by the rains.